Cascade Catalytically Released Nitric Oxide‐Driven Nanomotor with Enhanced Penetration for Antibiofilm. Issue 52 (7th November 2022) - Zheng, Jia; Wang, Wei; Gao, Xinyu; Zhao, Senfeng; Chen, Wansong; Li, Jianghua; Liu, You‐Nian
Abstract: Nanodrugs are becoming increasingly important in the treatment of bacterial infection, but their low penetration ability to bacterial biofilm is still the main challenge hindering their therapeutic effect. Herein, nitric oxide (NO)‐driven nanomotor based on L‐arginine (L‐Arg) and gold nanoparticles (AuNPs) loaded dendritic mesoporous silica nanoparticles (AG‐DMSNs) is fabricated. AG‐DMSNs have the characteristics of cascade catalytic reaction, where glucose is first catalyzed by the asymmetrically distributed AuNPs with their glucose oxidase (GOx)‐ mimic property, which results in unilateral production of hydrogen peroxide (H2 O2 ). Then, L‐Arg is oxidized by the produced H2 O2 to release NO, leading to the self‐propelled movement. It is found that the active movement of nanomotor promotes the AG‐DMSNs ability to penetrate biofilm, thus achieving good biofilm clearance in vitro. More importantly, AG‐DMSNs nanomotor can eliminate the biofilm of methicillin‐resistant Staphylococcus aureus (MRSA) in vivo without causing damage to normal tissues. This nanomotor provides a new platform for the treatment of bacterial infections. Abstract : Nitric oxide (NO)‐driven nanomotor based on L‐Arg and AuNPs loaded dendritic mesoporous silica nanoparticles (AG‐DMSNs) is fabricated. The cascade catalytically released NO‐driven nanomotor can trigger the autonomous movement. The NO‐driven nanomotor can penetrate deeply into biofilm, which disperses EPS and destroys bacterial cell membrane.